Online Shoppers’ Priority Attributes in Egypt - Soliman, Sally (AUC Knowledge Fountain, 2021)
E-commerce and online shopping have been among the world's fast-growing trends in the past few years. Each year the number of e-commerce deals grows enormously. Furthermore, the tendency will continue because many people are constricted by work and household duties. Simultaneously, the Internet saves much time and allows having a full shopping experience from the comfort of one's home. With the improvement of technology and the continuous progression in web development, retailers are not only seeking e-commerce to expand their sales, but the trend of full online retailing with no physical existence is becoming widespread. Given the expansion, it is becoming challenging for e-retailers to maintain their customers since consumers can easily compare the platforms and pick to place their orders at the platform that best meets their needs. To prevent this fast customer turnover, it is important to consider the consumers' preferences when online shopping to meet their needs better and locate their investments accordingly. This study holds a new perspective in presenting the service business's packaging by materializing the e-commerce business as an example. The author develops a model that guides in enhancing online platforms' efficiency based on online shoppers' preferences and priority attributes. These attributes are considered the packaging elements that augment the main business aspects summarized in the 7 Ps marketing mix module. In the context of interpreting the marketing orientation theory, the study measures consumers' priority attributes, summarized in the E-SERVPACK Model, in online shopping in four different product categories. Results revealed that the highest and lowest priority attributes are common across all four categories, yet the importance level differs from one category to another. It is advised that e-retailers consider developing their platforms and allocate their budgets based on their target consumers' preferences and the business's product type.